Long‐term follow‐up of children with in utero exposure to sulfonylurea medications - Marissa S. Rodenstein; Monica E. Bianco; Maegan U. Ramchal; Michael Murias; Rebecca L. Silton; Jami L. Josefson (Wiley, 2021)
Abstract Background Offspring born to mothers with gestational diabetes mellitus (GDM) are more likely to have negative neurodevelopmental health outcomes, early obesity, type 2 diabetes, and metabolic syndrome in childhood, adolescence, and adulthood. Standard of care management for GDM and type 2 diabetes mellitus during pregnancy is insulin, but oral sulfonylurea use is increasing, and these medications cross the placenta. Literature on treatment with sulfonylureas for maternal GDM has focused on maternal glycemic control and neonatal outcomes. Studies that have evaluated the long‐term outcomes of children exposed to sulfonylureas in utero are limited. Objective This study evaluated anthropometric and neurodevelopmental outcomes of 55 children (ages 5-10) born to mothers with diabetes during pregnancy treated with sulfonylurea or insulin. Methods and Results A group of 25 sulfonylurea‐exposed and 30 insulin‐exposed participants were age‐ and sex‐matched between groups. No significant differences were identified in z‐scores for body mass index (BMI), waist circumference, skinfold measurements, and body fat or rates of overweight/obese BMI between groups. On performance‐based cognitive assessment, the sulfonylurea‐exposed group had significantly lower scores on inhibition (p = 0.043). Conclusion In summary, children with in utero sulfonylurea exposure had similar physical measurements compared to children with insulin exposure and lower performance on a measure of executive function (inhibition), which is associated with adverse health outcomes.